Triple helix and residential development in a science and technology park: the role of intermediaries - Friederike Bellgardt; Jürgen Gohlke; Henriette Haase; Roman Parzonka; Juliane Schicketanz (Triple Helix, 2014)
Science and technology parks are the three-dimensional expression of the ever-growing importance of innovation, creativity and knowledge as economic resources. Science cities are the next step up: knowledge-based forms of urban settlement. Thanks to a housing project currently being developed, the Berlin-Adlershof science and technology park is undergoing a gradual transformation into a science city. Taking Berlin-Adlershof as a case study, this article examines the extent to which the triple helix approach can be usefully applied to the planning process of a housing project. The triple helix approach has hitherto been mainly used to study the organizational arrangements of industry, university and government, arrangements that are seen to foster processes of innovation. Drawing upon this tenet, the present study focuses on the socio-cultural aspects of urban development in the context of science cities, aspects which have so far received little attention in triple helix research. The aim is to use the triple helix concept to assess the innovative character of the gradual transformation of a science and technology park into a science city through residential development. Within the framework of this study, semi-structured expert interviews with representatives relevant to the Adlershof development were conducted between November 2013 and January 2014. The study showed that the triple helix approach cannot be usefully applied to the interaction of actors involved in residential development in science cities. Alternatively, we propose a model of interaction that highlights the pivotal role of the intermediary in the planning process.
Keywords: 330; Triple helix; Berlin-Adlershof; Residential development; Science and technology park; Science city